A rapid colorimetric lateral flow test strip for detection of live Salmonella Enteritidis using whole phage as a specific binder - Charlermroj, Ratthaphol; Makornwattana, Manlika; Phuengwas, Sudtida; Karoonuthaisiri, Nitsara (Frontiers in Microbiology, 2022)
Antibody is an important biomolecule binder indicating specificity of an immunoassay. To produce an antibody specific for live bacterial pathogens, the immunization using the live pathogens can be problematic. Phage display technology has become one of the most effective alternatives to select peptides, proteins and antibody binders with desirable specificity without an in-vivo production. In this study, we demonstrated the power of a microarray-based technique by screening for specific phage-derived antibody fragments against an important foodborne pathogen Salmonella. Furthermore, we successfully developed a lateral flow test for live Salmonella detection using the selected phage-displayed antibody fragments as a biological specific binder. The developed lateral flow test strips showed high specificity to Salmonella Enteritidis without cross-reactivity to eight serovars of Salmonella and other bacteria strains. Assay time of this method was only 15 minutes, whereas the conventional biochemical and serological confirmation test requires 24 hours. The developed screening technique and detection method can be applied for other foodborne pathogens or any targets of interest.